Development of Interactive Reading Multimedia Based on Educational Games for Grade I Students of Inpres Malakaya Elementary School, Gowa District - Aliem Bahri; Febrianti; Encik Savira Isnah; M. Kharis (Nusantara Science and Technology Proceedings, 2024)
The development of interactive reading multimedia based on educational games for grade I students of SD Inpres Malakaya is motivated by students' issues, such as difficulty distinguishing similar letters and challenges in reading fluency and word formation. Teachers still rely on thematic books for teaching reading, which may lack student interest. This issue is exacerbated by the COVID-19 pandemic, preventing teachers from conducting direct guidance. This research is a Research and Development (R&D) study using the modified 4D model, encompassing three stages: define, design, and develop. The instruments include questionnaires for media and subject matter experts to assess product validity, and for students and teachers to evaluate product feasibility. Validation results by media experts yielded an overall score of 66, with a percentage of 88%, categorized as "highly Valid". Validation by subject matter experts resulted in an overall score of 65, with a percentage of 86.6%, also categorized as "highly Valid". Evaluation by grade I students of SD Inpres Malakaya yielded an overall score of 70, with a percentage of 93.3%, categorized as "Very Feasible". Meanwhile, the evaluation by the class teacher produced an overall score of 69, with a percentage of 89.3%, categorized as "Very Feasible". This demonstrates that interactive learning multimedia can be used as a teaching medium in the school and can be developed for use in various schools.